Power allocation for the network coded cognitive cooperative network - Kaiser, Moritz Shamim (© 2011 IEEE, 2016)
7th International Conference on Wireless Communications, Networking and Mobile Computing, WiCOM 2011; Wuhan; China; 23 September 2011 through 25 September 2011 [© 2011 IEEE]. The conference paper's definite version is available at: https://doi.org/10.1109/wicom.2011.6036638